Macaulay's Minute Revisited: Colonial Language Policy in Nineteenth-century India - Evans, Stephen (Journal of multilingual and multicultural development, 2002)
This paper examines a crucial episode in the history of language policy in British colonial education: the Orientalist-Anglicist controversy of the 1830s over the content and medium of government education in India. The bitter dispute over colonial language-in-education policy during this period raised fundamental questions about the roles and status of the English language and the Indian vernacular and classical languages in the diffusion of Western knowledge and ideas on the subcontinent. At the heart of many accounts of the controversy, not least those of a polemical nature, is Thomas Babington Macaulay's famous Minute of 1835, which advocated the creation of a class of anglicised Indians who would serve as cultural intermediaries between the British and their Indian subjects. This paper reassesses Macaulay's influence on British language policy in 19th century India. It begins by examining the background to the Orientalist-Anglicist dispute in the late 18th and early 19th centuries, and then moves on to analyse the content and purpose of the Minute. The second part examines the short-term and long-term consequences of Macaulay's scheme in India and in other British colonial contexts.